Insuffisance Rénale Aigue Post-Opératoire Au Centre Hospitalier Universitaire Et Départemental Du Borgou : Fréquence Et Facteurs De Risques Associés - Séraphin, Ahoui; Adrien, Hodonou Montcho; Alexandre, Allode Salako; Blaise, Tchaou; Jacques, Vigan; Roméo, Agbidinoukoun; Kabibou, Salifou (European Scientific Journal, ESJ, 2016)
Introduction: Acute renal failure (ARF) post-operative is a specific form of acute deficiencies causing multiple declining factors. Objective: This survey aims to study the incidence and risk factors associated with acute renal failure (ARF) in post-operative surgical intensive care units to University Hospital of Borgou (UH-B): during 2015. Patients and Methods this study is a cross sectional, descriptive and analytical ones with the prospective data collection from March 1st to August 31th, 2015. The research has involved all patients admitted to the operating room for surgery and motherhood whatever reason and then transferred respectively to the intensive care areas at UH-B. The postoperative ARF has been investigated inner patients following inclusion criteria and classification according to RIFLE score. The socio-demographic, clinical and biological variables monitoring, even support and evolution are experimented. A questionnaire is designed for data collection. Data are analyzed by Epi-Info means with 5% of significance level. Results: 130 patients are registered. The mean age is 27.68 ± 12.87 years. The sex ratio is 0.66. The frequency of post-operative ARF reaches 12.31%. The associated risk factors are: hypertension (p = 0.0018), diabetes (p = 0.002), heart failure (p = 0.0104), severe sepsis (p = 0.006) hypovolemic shock (p = 0.002), ASA class ≥ 3 (p = 0.0014), preeclampsia-eclampsia (p = 0.012), the Altémier class classification ≥ 3 (p = 0.0164), a pathological urinary sediment like a proteinuria (p=0.006), haematuria (p= 0.001) and nitrituria (p=0.007). Consequently, three (03) subjects out of sixteen (16) have died (18.75%). Conclusion: The post-operative ARF is a reality in University Hospital Borgou , with a higher mortality rate. Thus, the prevention strategy is the best treatment through the screening and monitoring promotion towards risk factors.